Pendampingan Mini Riset Pelaksanaan Pembelajaran Pjok Di MIS Alkhairaat Kota Gorontalo) - Pomatahu, Aisah R.; Pauweni, Mirdayani; Said, Hariadi; Harianto, Arif (-, 2025)
The purpose of this service is to assist and monitor mini research on the implementation of PJOK learning carried out by 1st semester students at MI Alkhairaat Gorontalo City. The activity stages consist of: preparation, implementation, and evaluation. Based on the evaluation, this activity was carried out well, based on the stages of the activity until the objectives of this service activity were achieved. In addition, students gained benefits, including: increasing understanding of the objectives of implementing PJOK in schools, recognizing the scope of physical education which is the material at MI Alkhairaat, and being able to distinguish between physical education and sports coaching.